(untitled) (Bangladesh Journal of Animal Science, 2017)
About ten genes responsible for small heat-shock proteins (sHSP) have been isolated from silkworm. sHSP19.9 is one of the important member among them. Heat-induced stability of the sHSP was investigated at 60ºC with 20 mM HEPES buffer pH 7.7 containing 10 mM NaCl (low-ionic strength). Along with it probable suppression of the aggregation was also examined. At the mentioned reaction medium, sHSP19.9 was observed to be aggregated on the concentration- and time-dependent manners. It was successfully suppressed with dithiothreitol (DTT), higher-ionic strengths, Cysteine residues modifications and molecular chaperone: sHSP20.8. Bang. J. Anim. Sci. 2017. 46 (1): 57-64